Curriculum tendencies on Music Education: uncertainty and permanency in an endless present - Carvalho, Celso do Prado Ferraz de; Carvalho, Mauricio Braz de (Revista Eletrônica de Educação, 2016)
These theses about postmodernity and their expressions on social reforms implemented since 1990, have been used and incorporated by the musical education, in the teaching and formation of the docent. The objective in this text is to reflect on this matter seeing it through the practical-reflective teacher and a pedagogy focused on the docent’s competences, in learning how to learn and the overvaluation of knowledges of the everyday experience. A search on the musical education literature, above all in articles published in Journal and Anais of ABEM (Brazilian Association for Music Education) of of the last ten years, suggest a large diffusion, in the music education field, of postmodern/ post-structuralist suppositions about social and cultural life. This dissemination happens parallely with a bigger embodiment and its conceptions of formation and knowledge. The Marxian reference states that these theses may produce a retreat of the theory, depoliticisation of the debate and impoverishment of the act of knowing. Keywords: Curriculum. Postmodernity. Docent formation. Musical teaching. Tendências curriculares no ensino de música: indefinição e permanência de um presente eterno Resumo As teses sobre a pós-modernidade, bem como a sua expressão nas reformas educacionais implementadas a partir da década de 1990, têm sido amplamente incorporadas pelo campo da educação musical, no ensino e na formação docente. Nosso objetivo neste texto é problematizar essa questão analisando os temas do professor prático-reflexivo e de uma pedagogia centrada em competências docentes, no aprender a aprender e na sobrevalorização dos saberes da experiência cotidiana. O levantamento na literatura da área baseado, sobretudo em artigos publicados na Revista e nos Anais da ABEM (Associação Brasileira de Educação Musical) nos últimos dez anos, sugere a larga difusão, no campo da educação musical, dos pressupostos pós-modernos/pós-estruturalistas acerca da vida social e cultural. Tal difusão se daria em paralelo à vasta incorporação das suas correlatas concepções de formação e conhecimento. A partir do referencial marxiano, afirma-se que essas teses podem produzir na educação um recuo da teoria, a despolitização do debate e o empobrecimento do ato de conhecer. Palavras-chave: Currículo. Pós-modernidade. Formação docente. Ensino de música.